Análisis de la distancia recorrida atendiendo a umbrales absolutos y relativos en árbitros de fútbol 11 y fútbol 7 durante partidos oficiales. [Analysis of the distance covered according to absolute and relative thresholds in eleven-a-side and seven-a-side soccer referees during official matches]. - Mario Sánchez; Javier Sánchez-Sánchez; María Villa del Bosque; David Solano-Suárez; Daniel Castillo (Ramón Cantó Alcaraz, 2020)
The aim of this study was to analyze the physical response of soccer referees eleven-a-side (AC11), assistant soccer referees (AA11) and soccer referees seven-a-side (AC7) during official matches, using absolute speed ranges and the maximum speed peak. (Peak velocity) individualized. 36 soccer referees (25.6 ± 4.7 years) participated in this study, refereeing a total of 36 soccer matches. The total distance covered and the percentage of distance covered at different intensities were recorded from absolute and relative ranges using the Peak velocity of the 40-m speed test. The main results indicated that AC11 covered a greater percentage of distance (p <0.05) at speeds greater than 7 km·h-1 and in ranges between 20 and 80% of the Peak velocity reached by each soccer referee compared to AA11 and AC7. Furthermore, while AC11 covered a greater distance (p <0.01) than AA11 at speed ≥ 19,1 km.h-1, no differences (p> 0.05) were found in the range 80-100% of the individual Peak velocity. The results obtained suggest that the demands of the game should not only be focused on understanding the physical response taking into account absolute values, but also taking into account the Peak velocity reached by the soccer referee.